Sistem Pengontrolan Lampu Gedung STMIK AMIK Riau Berbasis IoT (Internet Of Things) - Rometdo Muzawi; Wahyu Joni Kurniawan (Jurnal Inovtek Polbeng Seri Informatika, 2018)
Internet of Things, also known as abbreviation IoT, is a hardware device (Raspberry Pi) that can connect to the internet with the aim of expanding the internet network connected to the hardware. The development of the Internet of things is a 4.0 technological revolution which is again the current trend. One of the uses of IoT technology is controlling room lights through an internet network that is controlled via a smartphone that can be operated remotely anywhere and anytime. But so far the control of the lights at STMIK Amik Riau is still done manually where security officers approach the swish button to turn on the lights. Therefore it is necessary to design a device that can control electronic equipment (lights) in real time. Where this study aims to build remote-controlled devices by utilizing internet technology to carry out an Internet of Things (IoT) based light control process. This research was conducted by building a prototype with python and mobile based programming applications. In this study there is a room lighting control feature with the first condition that one lamp is used to turn on a lamp and the second condition is used to turn on the lights simultaneously and coupled with camera modules to monitor the condition of the room